Studi Komparasi Perilaku Kreatif Mahasiswa Menghadapi Dunia Kerja (Pada Mahasiswa Jurusan Manajemen FEB di UTM) - Anis Binti Hamed; Mochammad Isa Anshori (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This research was conducted to find out how students'creative behavior in facing the world of work. The research method used in this research is to use qualitative methods.And this research uses purposive sampling technique, namely the method of taking informants or data sources with certain considerations or certain criteria. These particular considerations, for example the person who is considered to know the most about what we expect, or maybe he is the ruler so that it will make it easier for researchers to explore the object or social situation to be studied. In this study using management students with the following criteria: 1. Trunojoyo Madura University students, 2.Management students, 3. 7th Semester Management students, 4. Students who after graduating from college want to work immediately. From the explanations of informants (A1, A2, A3, A4, and A5) who have been interviewed, the factors that encourage students after graduating from college to want to work immediately differ from one another. Some are caused by impulses from within himself (internal factors) and some are caused by encouragement or stimulation from the outside environment (external factors). However, most of the statements from the informants were influenced by internal factors, namely the desire of themselves, but some were influenced by external factors such as support from parents that made the informant melt and thought that the parents' decision must be the best    for him and the informant accepted suggestions from his parents. So it can be concluded that internal factors have a stronger influence because based on the statements of the five informants, four of the informants chose the job because of their own desires, and some were suggested by their parents and students could accept the sesuggestions without an element of coercion because after consideration it was goodness for him.